A MICE - Nasywa Putri, Nadiya; Syah, Firman (Bisnis Event, 2025)
. As a major event involving thousands of participants and visitors, the smooth operation and management of the event heavily rely on an efficient and modern system, particularly in the registration and ticket management process. To support this, the use of digital platforms like Ticket Tailor becomes a relevant solution. Ticket Tailor, a web-based application, offers convenience in ticket sales and management, with key features such as integrated payment systems, customizable ticket designs, and efficient participant registration management. This application helps reduce human error, improves operational efficiency, and ensures the validity and security of tickets. The implementation of Ticket Tailor by GCM Group, the organizer of JFW, can optimize ticket management, streamline the registration process, and enhance user experience, leading to higher participant satisfaction. Therefore, the utilization of this technology contributes positively to creating a more organized, modern event that aligns with the evolving needs of the times and supports the overall success of Jakarta Fashion Week. Keyword: Event Ticketing, Ticket Tailor, participant registration, , web-based platform